2007
DOI: 10.1029/2006gl027472
|View full text |Cite
|
Sign up to set email alerts
|

Radiative forcing due to stratospheric water vapour from CH4 oxidation

Abstract: [1] Here we report on estimates of the changes in stratospheric water vapour (SWV) due to methane oxidation based on observational data. Above the tropopause oxidation of methane results in a decrease in its mixing ratio with altitude and this is a major source for SWV. The vertical profile of SWV changes from methane oxidation is presented here using satellite observations of the vertical profile of methane. Trends in the SWV are shown to be small in the lower stratosphere, but can reach 0.7 ppbv at 30 km at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…Stated RFs are based on composition changes in the troposphere and do not include stratospheric response, although some studies also include the lower stratosphere, where aviation NOx also increases O 3 (e.g., 15) and the greenhouse effect is similar to the upper troposphere. The CH 4 RF here also excludes changes to stratospheric water vapor, which are estimated to increase RF cooling by about 15% (24). Transient CH 4 perturbations for any particular year are always less than predicted at steady state due to the decadal lifetime of CH 4 and the steadily increasing aviation emissions (25).…”
Section: Rf Uncertainty From Model Ensemblesmentioning
confidence: 99%
“…Stated RFs are based on composition changes in the troposphere and do not include stratospheric response, although some studies also include the lower stratosphere, where aviation NOx also increases O 3 (e.g., 15) and the greenhouse effect is similar to the upper troposphere. The CH 4 RF here also excludes changes to stratospheric water vapor, which are estimated to increase RF cooling by about 15% (24). Transient CH 4 perturbations for any particular year are always less than predicted at steady state due to the decadal lifetime of CH 4 and the steadily increasing aviation emissions (25).…”
Section: Rf Uncertainty From Model Ensemblesmentioning
confidence: 99%
“…It is also possible to have a two-stage process, where convection lofting parcels and ice rise to the upper troposphere, followed by gradual dehydration as the parcels ascend into the stratosphere (Rosenlof 2003). The 3 rd pathway has been considered as insignificant in the lower stratosphere (e.g., Rosenlof 2003;Myhre et al 2007). This leaves either the first or the second pathway and no definite conclusion has been reached as to which is the major pathway for water to rise into the stratosphere .…”
Section: Introductionmentioning
confidence: 99%
“…16,[24][25][26] However, it was shown that a computed stratospheric temperature change caused by increasing stratospheric water vapor is strongly dependent on the temporal and spatial variation of stratospheric water vapor changes. 22,63,64 A more realistic change in the stratospheric water vapor profiles yields a weaker stratospheric cooling than for a constant profile. 22,63,64 In particular, Myhre et al 64 (2007) calculated a stratospheric cooling of about 0.0 K to 0.2 K in the lower polar stratosphere (z15-25 km) caused by stratospheric water vapor increase due to CH 4 oxidation based on observational data for the time period from 1979 until 2000.…”
Section: Impact On Ozone-climate Interactionsmentioning
confidence: 99%
“…22,63,64 A more realistic change in the stratospheric water vapor profiles yields a weaker stratospheric cooling than for a constant profile. 22,63,64 In particular, Myhre et al 64 (2007) calculated a stratospheric cooling of about 0.0 K to 0.2 K in the lower polar stratosphere (z15-25 km) caused by stratospheric water vapor increase due to CH 4 oxidation based on observational data for the time period from 1979 until 2000. The amount and the spatial distribution of stratospheric water increase calculated by Myhre et al 64 (2007) are comparable to the water vapor increase inferred for a potential future hydrogen economy (see Fig.…”
Section: Impact On Ozone-climate Interactionsmentioning
confidence: 99%